Two new records in Orchidaceae (Vanillinae) from southernmost Colombian Amazonia: Vanilla javieri, a new species, and Vanilla appendiculata - Barona-Colmenares, Andrés A. (Phytotaxa, 2018)
This paper deals with two new records for the genus Vanilla in the Colombian Amazonia. Both species are part of the Vanilla planifolia group and exhibit fleshy leaves with conspicuous petioles, greenish flowers with concave lips, a well-defined penicillate callus and recurved lip apices with small papillae. The new species, Vanilla javieri, is easily distinguished by its habit as a small understory hemiepiphyte vine with terminal inflorescences exhibiting a basal, non-floriferous, sub-cordate foliaceous bract; small greenish cream-colored flowers with a glabrous ventral surface of the column and a strongly reflexed lip apex adorned by few digitiform papillae; along with highly aromatic fruits that are pendant, basally arcuate, rather stout and obscurely calyculate. The new species is sympatric and closely related to Vanilla appendiculata, reported here for the first time in Colombia. Botanical descriptions and photographs are presented for both species.